Program Pembinaan Al-Qur’an Menuju Generasi Qur’ani di Kabupaten Sidenreng Rappang - Dewi Indriani; Rahmayani L. (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
Real Work Lecture (KKN) STIBA Makassar Batch IV in Sidenreng Rappang Regency aims to perform community service as a form of Tri Dharma Perguruan Tinggi. The method of implementation of the service program begins by mapping the problems and needs of the community using SOAR Analysis. After the analysis is done, the work program is arranged according to the needs of the community. Successful work programs are the Teaching of the Qur'an, Teaching Arabic, Taklim Muslimah and The Festival of the Pious Children. All this work program has been implemented and showed good initial results and will be followed up by Muslimah Wahdah of Sidenreng Rappang Regency.